Design Of A Security System Tool For Tapis Fabric Object In Lampung Museum Based On Internet Of Things (IoT) Technology - Purwiyanti, Sri; Irawan, Dery; Herlinawati, Herlinawati (Journal of Engineering and Scientific Research, 2024)
The Lampung Museum has many historical collections, one of which is tapis cloth. The tapis cloth collection at the Lampung Museum is still not safe because the layout is still open and the distance is far from CCTV. This study aims to design a series of security systems using two Passive Infra Red (PIR) sensor inputs and a buzzer output and a VC0706 camera at the Lampung Museum which can be monitored directly remotely with notifications on the Telegram platform. The research method used is design and testing (subsystem testing and overall system testing). The data from this research are the results of system design, how the security system works on filter cloth objects and the overall system. The security system was tested using Telkomsel, Indosat and Tri providers. The results obtained for image quality 640 x 480 Pixels obtained an average delivery time from Telkomsel providers for 25.2 seconds, providers for Indosat 27.4 seconds and Tri providers for 28.6 seconds. then an experiment was carried out with 3 different image qualities, namely 640 x 480 Pixels, 320 x 240 Pixels and 160 x 120 Pixels with Telkomsel provider with an average sending value for image quality 640 x480 Pixels for 25.2 seconds, image quality 320 x 240 Pixels for 20.5 seconds and 160 x 120 Pixel image quality for 17.7 seconds. Then testing sending Telegram notifications remotely from a security system tool and obtained that the time sent notifications from the Arduino IDE serial monitor is the same as the time received notifications on the Telegram platform, which means sending notifications takes place in real time. The Lampung Museum has many historical collections, one of which is tapis cloth. The tapis cloth collection at the Lampung Museum is still not safe because the layout is still open and the distance is far from CCTV. This study aims to design a series of security systems using two Passive Infra Red (PIR) sensor inputs and a buzzer output and a VC0706 camera at the Lampung Museum which can be monitored directly remotely with notifications on the Telegram platform. The research method used is design and testing (subsystem testing and overall system testing). The data from this research are the results of system design, how the security system works on filter cloth objects and the overall system. The security system was tested using Telkomsel, Indosat and Tri providers. The results obtained for image quality 640 x 480 Pixels obtained an average delivery time from Telkomsel providers for 25.2 seconds, providers for Indosat 27.4 seconds and Tri providers for 28.6 seconds. then an experiment was carried out with 3 different image qualities, namely 640 x 480 Pixels, 320 x 240 Pixels and 160 x 120 Pixels with Telkomsel provider with an average sending value for image quality 640 x480 Pixels for 25.2 seconds, image quality 320 x 240 Pixels for 20.5 seconds and 160 x 120 Pixel image quality for 17.7 seconds. Then testing sending Telegram notifications remotely from a security system tool and obtained that the time sent notifications from the Arduino IDE serial monitor is the same as the time received notifications on the Telegram platform, which means sending notifications takes place in real time.